What's new in Microsoft® Office 2003 - Manning, Cheryl (McGraw-Hill / Irwin, 2005)
Contens: What's New in Office 2003; What's New in Word 2003; What's New in Excel 2003; What's New in Powerpoint 2003; What's New in Access 2003; What's New in Outlook 2003